2022
DOI: 10.1371/journal.pone.0275725
|View full text |Cite|
|
Sign up to set email alerts
|

Myoglobin regulates fatty acid trafficking and lipid metabolism in mammary epithelial cells

Abstract: Myoglobin (MB) is known to bind and deliver oxygen in striated muscles at high expression levels. MB is also expressed at much reduced levels in mammary epithelial cells, where the protein´s function is unclear. In this study, we aim to determine whether MB impacts fatty acid trafficking and facilitates aerobic fatty acid ß-oxidation in mammary epithelial cells. We utilized MB-wildtype versus MB-knockout mice and human breast cancer cells to examine the impact of MB and its oxygenation status on fatty acid met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Towards a possible function of this ectopically expressed MB protein, it should be noted that the globin occurs exclusively within luminal cells (as opposed to myoepithelial cells) in healthy and malignantly transformed mammary epithelia of ´mice and men´ 3 , thus suggesting MB to also function as a fatty acid carrier in vivo. This O 2 -dependent shuttling of C16 saturated and C18 monounsaturated fatty acids by MB was already implied in earlier in vitro studies 8 11 and further substantiated in a recent study from our group 12 . Beyond the mammary gland, we also demonstrated that the presence of MB in the brown adipose tissue (BAT) of mice appears to link oxygen and lipid-based thermogenic metabolism by shifting the lipid droplet (LD) equilibrium towards higher counts of smaller droplets (i.e., towards a browning phenotype) 13 .…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Towards a possible function of this ectopically expressed MB protein, it should be noted that the globin occurs exclusively within luminal cells (as opposed to myoepithelial cells) in healthy and malignantly transformed mammary epithelia of ´mice and men´ 3 , thus suggesting MB to also function as a fatty acid carrier in vivo. This O 2 -dependent shuttling of C16 saturated and C18 monounsaturated fatty acids by MB was already implied in earlier in vitro studies 8 11 and further substantiated in a recent study from our group 12 . Beyond the mammary gland, we also demonstrated that the presence of MB in the brown adipose tissue (BAT) of mice appears to link oxygen and lipid-based thermogenic metabolism by shifting the lipid droplet (LD) equilibrium towards higher counts of smaller droplets (i.e., towards a browning phenotype) 13 .…”
Section: Introductionsupporting
confidence: 82%
“…Our earlier observation in brown adipose tissue correlated loss of MB with bigger lipid droplets, even though the overall lipid content didn’t differ 13 . Moreover, in the mammary epithelial cells, we also showed that MB plays a role in the trafficking of fatty acids in an O 2 -dependent manner 12 . Our current results suggest that the loss of MB in the WapCre;Trp53 flox /MB tumors, which associates with a higher load of entrapped fat in the cells, could either be explained by an increased invasive behavior of the tumor to the pre-existing mammary adipose tissue, or by the fact that the tumor cells themselves are accumulating more lipid droplets, or that cancer stem cells increasingly differentiate into adipocytes, a mechanism has been demonstrated to be induced in tumor cells undergoing EMT 31 .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The nonspecific binding of polysulfides has been observed in the reaction of human methemoglobin with sulfide . Previous reports on the binding of nonpolar species to myoglobin have been presented; for example the nonspecific binding of fatty acids to myoglobin is considered to participate in their trafficking and metabolism. It should be considered that it cannot be ruled out that polysulfides may be below the limit of detection by cold cyanolysis under the reaction conditions selected.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works have outlined the ability of FFA, particularly medium-chain (C 16 –C 18 ) fatty acids, to bind the heme protein, oxymyoglobin (Mb). , However, this work made little mention of the influence of FFA binding on the Mb redox status. Recently, it was reported that linoleic acid (LA) can interact with turkey met-hemolysate, producing a bis-histidyl ferric (Bis-His) Hb species, more commonly known as hemichrome , which strongly inhibited lipid oxidation compared to native met-hemolysate .…”
Section: Introductionmentioning
confidence: 99%